A localized molecular automaton for in situ visualization of proteins with specific chemical modifications. Issue 6 (10th January 2020) - Liu, Lu; Li, Siqiao; Mao, Anwen; Wang, Guyu; Liu, Yiran; Ju, Huangxian; Ding, Lin
Abstract : A localized DNA automaton is reported for in situ visualization of a specific protein subtype with dual chemical modifications on the cell surface, which executes protein-confined computation according to an anticoding – coding propagation algorithm. Abstract : Given the powerful regulation roles of chemical modification networks in protein structures and functions, it is of vital importance to acquire the spatiotemporal chemical modification pattern information in a protein-specific fashion, which is by far a highly challenging task. Herein, we design a localized DNA automaton, equipped with an anticoding – coding sequential propagation algorithm, for in situ visualization of a given protein subtype with two chemical modifications of interest on the cell surface. The automaton is composed of three probes respectively for the protein and two types of modifications. Once anchored on the cell surface and triggered, the automaton performs sequential protein-localized, DNA hybridization-based computations on the proximity status of each modification type with the protein and contracts the set of close proximity information into a single fluorescence signal turn-on using the designed algorithm. The modular and scalable features of the automaton enable its operation in scaled-down versions for protein-specific identification of one given modification. Thus, this work opens up the possibility of using automata for revealing complex regulation mechanisms of protein posttranslational modifications.